RELATIONSHIP AMONG ENERGY, BIOENERGY, AND AGRICULTURAL COMMODITY PRICES: RE-CONSIDERING STRUCTURAL CHANGES - Mehdi Nemati (International Journal of Food and Agricultural Economics, 2018)
This study investigates the relationships among the prices of gasoline, ethanol, and agricultural products that include soybeans and corn. By increasing production of ethanol using corn, concerns about emerging new relationship between agricultural products price and energy price increased. The result indicates that, without considering structural breaks, there is no long-run relationship between energy and agricultural products prices. However, after consideration of structural breaks not only, long-run relationship between energy and agricultural products exist, but also this relationship intensified during last decade. Also, energy price can be transmitted to agricultural products prices from the indirect and direct channel.